Legal deposit in Lithuania in 1945 - 1992 - Ringailė Bagušytė (Knygotyra, 2024)
The article describes in detail the development of legal deposit in Lithuania from 1945 to 1992, with a major focus on the documents regulating legal deposit and the control methods applied to the delivery of these documents.